Strategic Risk’s Variation as a function of Competitive Intelligence Investment - An applied research on some Iraqi’s manufacturing Companies – - اسماعيل مصطفى منير; جميل بسام باسم (Journal of Economics and Administrative Sciences, 2016)
ABSTRUCT The main aim of this research has been associated with the study of relationship between competitive intelligence and strategic risk, and to deduct their specific trends, which are interpreted as predicted by research hypotheses according to a review of literature including prior studies. The basic theme of these hypotheses is related to the probability that declining levels of strategic risk and competitive positions of industrial companies is dependent upon the growing capacity to stay ahead of competitors in the market. A purposive non-random sample has selected consisting of (30) thirty Iraqi industrial joint stock companies listed on the Iraq Stock Exchange along a time horizon lasted (10) years (2003-2012). Variables were measured and analyzed, both financially and statistically, on the level of description and interpretation using the ordinal approach for building a probabilistic transition matrices towards estimating strategic risk levels. Moreover, a number of statistical tools has used for statistical description, interpretation and inference, which are measures of central tendency, dispersion, correlation and regression respectively. The required mathematical analyses on companies’ data and the four research’s hypotheses have tested and conducted on the sample studied after being classified into three minor ones. Then, it has reached to many conclusions confirm research’s hypotheses in their prediction on the ability of competitive intelligence, with the resulting investment returns, to interpret the varying levels of strategic risk. A number of recommendations have proposed initiating the need to monitor the movements of competitors and analyze their responses to customers in a dynamic environment. The research has also proposed a number of future works that may exceed the current determinants or being prepared on other designs as a continuous scientific investigation for studying interrelationships of phenomena.